(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The challenges of the globalization.In the paper it is researched a payment system. It is characterized its advantages and disadvantages and analyzed the directions of its improvement because of globalization. It is found factors, which impact on the employment and wages. It is researched the trends to change payment systems in the modern conditions of development.